Data feminism - D'Ignazio, Catherine; Klein, Lauren F. (The MIT Press, 2020)
"A new way of thinking about data science and data ethics that is informed by the ideas of intersectional feminism. Today, data science is a form of power. It has been used to expose injustice, improve health outcomes, and topple governments. But it has also been used to discriminate, police, and surveil. This potential for good, on the one hand, and harm, on the other, makes it essential to ask: Data science by whom? Data science for whom? Data science with whose interests in mind? The narratives around big data and data science are overwhelmingly white, male, and techno-heroic. In Data Feminism, Catherine D'Ignazio and Lauren Klein present a new way of thinking about data science and data ethics–one that is informed by intersectional feminist thought. Illustrating data feminism in action, D'Ignazio and Klein show how challenges to the male/female binary can help challenge other hierarchical (and empirically wrong) classification systems. They explain how, for example, an understanding of emotion can expand our ideas about effective data visualization, and how the concept of invisible labor can expose the significant human efforts required by our automated systems. And they show why the data never, ever 'speak for themselves.' Data Feminism offers strategies for data scientists seeking to learn how feminism can help them work toward justice, and for feminists who want to focus their efforts on the growing field of data science. But Data Feminism is about much more than gender. It is about power, about who has it and who doesn't, and about how those differentials of power can be challenged and changed."-
Keywords: approches et analyses; discipline; données scientifiques; histoire et politique; intersectionnalité; patriarcat; privilèges; projet charge mentale; pédagogie; racisme; rapports de pouvoir; ressource en ligne; sciences; sciences humaines; systèmes d'oppressions; thématiques; travail; travail scientifique; épistémologie

Je suis un monstre qui vous parle: rapport pour une académie de psychanalystes - Preciado, Paul B. (Grasset, 2020)
« La psychanalyse est face à un choix historique sans précédent : soit elle continue à travailler avec l'ancienne épistémologie de la différence sexuelle et légitime de facto le régime patriarco-colonial qui la soutient, devenant ainsi responsable des violences qu'elle produit, soit elle s'ouvre à un processus de critique politique de ses discours et de ses pratiques. Continuer à pratiquer la psychanalyse en utilisant la notion de différence sexuelle, avec des instruments cliniques comme le complexe d'OEdipe, est aussi aberrant que de prétendre la terre plate. Le temps est venu de sortir les divans sur les places, collectiviser la parole, politiser les corps, débinariser la sexualité et décoloniser l'inconscient : la survie de la psychanalyse est à ce prix. »– Quatrième de couverture.
Keywords: approches et analyses; corps; cours; cycles supérieurs; discipline; discours dominant; fem7000; identités LGBTQIA2+; patriarcat; personnes trans*; sciences humaines; systèmes d'oppressions; thématiques; violences; épistémologie